Childhood Pseudoxanthomatousmastocytosis; Report of two cases - Bhabani S. T. P. Singh; Tapaswini Tripathy; Bikash Ranjan Kar; Surabhi Singh (Wolters Kluwer Medknow Publications, 2018)
Cutaneous mastocytosis (CM) is a mast cell proliferative disorder that commonly affects pediatric population. It has various clinical forms such as urticaria pigmentosa, solitary mastocytoma, telangiectasia macularis eruptiva perstans, diffuse CM, and erythrodermic mastocytosis. Pseudoxanthomatous mastocytosis is a type of diffuse CM, which is relatively rare. It can mimic xanthoma disseminatum, juvenile xanthogranuloma, and benign cephalic histiocytosis which are also seen commonly in children but have different prognostic behavior. Hence, high degree of clinical suspicion along with histopathology is required for the diagnosis. Herein, we report two cases of childhood pseudoxanthomatous mastocytosis.